2015
DOI: 10.1111/1462-2920.13061
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of Rhizobiaceae communities inhabiting soils, root surfaces and nodules reveal a strong selection of rhizobial partners by legumes

Abstract: Current knowledge about rhizobial diversity patterns in non-nodule habitats is scarce, limiting our understanding of basic aspects of rhizobial ecology like competitiveness for nodule occupancy and host effects on community structure. We used a combination of cultivation-dependent and independent approaches to analyse alpha and beta diversity patterns of Rhizobiaceae communities from a conserved seasonally dry tropical forest site in central Mexico and two nearby agricultural fields. Lineage-specific recA ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 91 publications
4
32
0
1
Order By: Relevance
“…Consistent with the results of Miranda‐Sanchez et al . (), our results demonstrated that the nodule bacteria (rhizobia) undergo a hierarchical filtration through bulk soil to the root by legume plants. In addition, our study indicated that both nonsymbiotic and symbiotic nodule endophytes are subjected to hierarchical filtration.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Consistent with the results of Miranda‐Sanchez et al . (), our results demonstrated that the nodule bacteria (rhizobia) undergo a hierarchical filtration through bulk soil to the root by legume plants. In addition, our study indicated that both nonsymbiotic and symbiotic nodule endophytes are subjected to hierarchical filtration.…”
Section: Discussionsupporting
confidence: 55%
“…); and nodule/bulk soil rhizobial communities of Acacia and Phaseolus vulgaris (Miranda‐Sanchez et al . ). This filtration was related to the effects of roots on nutrient supply and the physicochemical features of the rhizosphere as well as to the change in environment from soil to endosphere (Gottel et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations